Effectiveness of purple leaves (Graptophyllum pictum L. Griff) and hydroxyapatite as socket preservation biomaterials - Ratri Maya Sitalaksmi; Rizkipriyanto Azharpratomo; Shafira Ninditya Irsan; Primanda Nur Rahmania; Sisca Meida Wati; Syafira Salsabila Adam; Kavanila Bilbalqish; Khairul Anuar bin Shariff; Harry Laksono; Agus Dahlan; Devi Rianti (Journal of Oral Biology and Craniofacial Research)
Background: Tooth extraction without socket preservation will lead to reduction in the dimensions and volume of the alveolar bone. Bone defects resulting from tooth extraction not only hinder prosthetic reconstruction but also present aesthetic issues and complicating dental implant treatment. Purple leaves contains flavonoids, steroids, tannins, saponins,and non-toxic alkaloids. These compounds play roles as antimicrobials, immunomodulators, antioxidants, anti-inflammatories, analgesics. Hydroxyapatite has good biocompatibility, and can induce osteoblast differentiation. Aim: To investigate the effects of the combining nanoemulsion extract of purple leaves and hydroxyapatite on the expression of RUNX2, OSX, OPN, ALP, and calcium deposition. Method: This research used MTT Assay, ICC, and Alizarin Red staining. The study groups were as follows: Group 1: Ad-MSCs; Group 2: Ad-MSCs + αmem; Group 3: Ad-MSCs + osteogenic medium + 1 % nano-extract of Purple leaves & Hydroxyapatite; Group 4: Ad-MSCs + osteogenic medium + 2 % nano-extract of Purple leaves & Hydroxyapatite. Observations were conducted on days 7, 14, and 21. Results: The combination of nanosuspension extract of Purple leaves and hydroxyapatite significantly increased the expression of RUNX2, OSX, OPN,ALP and calcium deposition compared to other groups. The combination of nanoemulsion extract of Purple leaves and hydroxyapatite were significant (P < 0.05) compared to the control group on each day 7, day 14 and day 21. Conclusion: The combination of nanosuspension extract of Purple leaves and hydroxyapatite was able to enhance the expression of RUNX2, OSX, OPN, ALP, and calcium deposition on days 7,14,21.